PEACE IN THE MIDST OF VIOLENCE: ANALYZING THE ROLE OF ELITES IN PRESERVING PEACE AND HARMONY IN MANADO - Muhammad Rivai Abbas (IAIN Surakarta, 2016)
The study attempts to look at the existing inter-religious peace and harmony in Manado. The focus is an attempt to compare between Manado and Ambon which are similar in terms of demographic composition, historical background, political and cultural values but at the same time both are different; the former was in conflict, while the latter was an area of peace during the conflict escalation that engulfed some parts of East Indonesia. This study also tries to look at the strategy of Christian and Muslim communities in both cities in dealing with social tensions. In addition, this article specifically tries to explain factors that contribute to the presence of peace in Manado and its absence in Ambon. Subsequently, attention is also paid to the impact and mechanisms used by the elite in maintaining peace in Manado. This study uncovers some interesting findings. First, there are five elements that support the existence of peace in Manado: education, cultural values (local wisdom), economic situations, spiritual understanding, and the role of the elite. Second, inter-religious peace and harmony can exist in Manado, because of the synergy and cooperation of these three levels of leadership. Third, although the theory of Lederach seems to suggest that top-level leaders are the most dominant element of the elite, it is found that the role of grassroots leaders including leaders of congregations (imam, ustadz, clergymen, and priests) is more vital as their more directly involved in the daily activities of society. Fourth, the mechanisms of these elites seem to be various in every stage of leadership.